2022
DOI: 10.1186/s40168-021-01194-8
|View full text |Cite|
|
Sign up to set email alerts
|

Microbial colonization and persistence in deep fractured shales is guided by metabolic exchanges and viral predation

Abstract: Background Microbial colonization of subsurface shales following hydraulic fracturing offers the opportunity to study coupled biotic and abiotic factors that impact microbial persistence in engineered deep subsurface ecosystems. Shale formations underly much of the continental USA and display geographically distinct gradients in temperature and salinity. Complementing studies performed in eastern USA shales that contain brine-like fluids, here we coupled metagenomic and metabolomic approaches t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
2

Relationship

2
4

Authors

Journals

citations
Cited by 9 publications
(8 citation statements)
references
References 75 publications
(88 reference statements)
1
7
0
Order By: Relevance
“…S7B). These findings are consistent with the dynamics in the lower-salinity STACK formation, where Thermotogae species were detected in high abundance [66]. Based on the findings of our 16S rRNA sequencing meta-study, lineages implicated with sulfide production are common regardless of salinity range, suggesting the sulfidogenic niche appears to be occupied throughout the formations considered here.…”
Section: Salinity Is a Key Driver Of Fractured Shale Microbiome Compo...supporting
confidence: 89%
See 1 more Smart Citation
“…S7B). These findings are consistent with the dynamics in the lower-salinity STACK formation, where Thermotogae species were detected in high abundance [66]. Based on the findings of our 16S rRNA sequencing meta-study, lineages implicated with sulfide production are common regardless of salinity range, suggesting the sulfidogenic niche appears to be occupied throughout the formations considered here.…”
Section: Salinity Is a Key Driver Of Fractured Shale Microbiome Compo...supporting
confidence: 89%
“…As noted above, the influence of salinity on community composition is strong, inducing physiological and thermodynamic constraints on the fractured shale microbiome [ 66 ]. We hypothesize that varying salinity levels lead to different organisms occupying similar niches in the shale microbiome, such as the potential to generate sulfide from thiosulfate or sulfur.…”
Section: Resultsmentioning
confidence: 99%
“…Spacers within CRISPR arrays therefore provide a record of past interactions between a host and viral population, and host-viral linkages can be made by matching the hosts' CRISPR spacers to protospacers in viral genomes (11,(15)(16)(17)(18)(19)(20)(21)(22)(23)(24)(25)(26)(27). However, the presence of CRISPR systems within the microbial community is often a limiting step to making strong host-virus connections; CRISPR defense is most likely advantageous in ecosystems where host and viral populations repeatedly interact, such as environments dominated by biofilms or those hosting lower microbial and viral diversity (28)(29)(30).…”
Section: Introductionmentioning
confidence: 99%
“…To address this knowledge gap, we used a temporally-resolved dataset from six subsurface fractured shale wells to interrogate host-virus dynamics and CRISPR arrays in a natural ecosystem. Subsurface fractured shales, which are relatively closed ecosystems with limited immigration, elevated temperatures, lower microbial diversity and likely dominated by biofilms, present an opportunity to address these questions through strong CRISPR-based host-viral linkages (21,23,4649). We hypothesized and found that CRISPR viral defense systems were widely encoded across hosts within shale microbial communities.…”
Section: Introductionmentioning
confidence: 99%
“…Following the publication of the original article [ 1 ], the author reported that Figs. 2 and 5 contains extra images at the topmost right that should have not been a part of these figures.…”
mentioning
confidence: 99%